Proposing a Mathematical Model to Expand Power Generation Capacity Considering Dispersed Generation Units to Decrease Carbon Dioxide - Ezzatollah Asgharizadeh (مدیریت صنعتی, 2017)
This study presents amathematical model for the development of power plants capacity to controlcarbon dioxide. The objective function of the model is to minimize the costs ofinvesting in new power plants, costs of fuels, costs of maintenance and socialcosts of carbon dioxide over the years from 2011 to 2025. The model has some constraintsincluding demand, development of renewable power plants and development of dispersedgeneration sites. The proposed model has been solved and analyzed in differentscenarios regarding approaches such as "economic and environmental", “economic”and “decreasing the costs of investment in renewable technologies”. It shouldbe noted that having conducted the first scenario, the sensitivity of themathematical model has been studied in relation to a number of parameters.These parameters include the efficiency of technologies, the social costs ofcarbon dioxide and the costs of maintaining power generation technologies. In thescenario with economic and environmental approach, combined cycle technologies,CHP, small wind and large wind; and in the economic approach, combined cycletechnology, CHP and large wind have been justified. Moreover, in the scenariowith the reduction of investment costs, variables related to renewabletechnologies, combined cycle technology, CHP, small wind, large wind andphotovoltaic have been taken into account.